Nontangential Limits for Modified Poisson Integrals of Boundary Functions in a Cone - Lei Qiao (Journal of Function Spaces and Applications)
Our aim in this paper is to deal with non-tangential limits for modified Poisson integrals of boundary functions in a cone, which generalized results obtained by Brundin and Mizuta-Shimomura.